Restricted Higher-Order Anti-Unification for Analogy Making - Krumnack, Ulf; Schwering, Angela; Gust, Helmar; Kühnberger, Kai-Uwe (AI 2007: Advances in Artificial Intelligence, 2007)
Anti-unification has often be used as a tool for analogy making. But while first-order anti-unification is too simple for many applications, general higher-order anti-unification is too complex and leads into theoretical difficulties. In this paper we present a restricted framework for higher-order substitutions and show that anti-unification is well-defined in this setting. A complexity measure for generalizations can be introduced in a quite natural way, which allows for selecting preferred generalizations. An algorithm for computing such generalizations is presented and the utility of complexity for anti-unifying sets of terms is discussed by an extended example.